2000
DOI: 10.1111/j.1572-0241.2000.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized placebo-controlled double-blinded pilot study of misoprostol rectal suppositories in the prevention of acute and chronic radiation proctitis symptoms in prostate cancer patients

Abstract: Misoprostol rectal suppositories significantly reduce acute and chronic radiation proctitis symptoms in patients receiving radiation therapy for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 35 publications
0
26
0
2
Order By: Relevance
“…PGE2 and the PG analogs enprostil and misoprostol (Cytotec®) display radiation protection in animal studies [119][120][121][122] . Misoprostol suppositories also reduced symptoms of acute radiation colitis in patients undergoing radiation therapy for prostate cancer [123] . With respect to the mechanism of action, PGE2 has pro-proliferative and anti-apoptotic effects on epithelial cells in gastrointestinal injury.…”
Section: Prevention Of Radiation Colitismentioning
confidence: 96%
“…PGE2 and the PG analogs enprostil and misoprostol (Cytotec®) display radiation protection in animal studies [119][120][121][122] . Misoprostol suppositories also reduced symptoms of acute radiation colitis in patients undergoing radiation therapy for prostate cancer [123] . With respect to the mechanism of action, PGE2 has pro-proliferative and anti-apoptotic effects on epithelial cells in gastrointestinal injury.…”
Section: Prevention Of Radiation Colitismentioning
confidence: 96%
“…By supplementing the diet with n(/3 PUFAs one might induce conversion to eicosanoids with less proinflammatory functions compared to the products of n(/6 PUFAs [5]. A pilot study with 16 prostate cancer patients receiving either external RT or external RT plus implants of brachytherapy showed that rectal suppositories with misoprostol, a PGE1-analogue, reduced proctitis symptoms 4 weeks after external RT [29]. However, no significant differences in histopathological or endoscopic scores could be found between six treated and five untreated patients.…”
Section: Measurements Related To Nutritionmentioning
confidence: 99%
“…Clinical studies show increased risk of delayed radiation enteropathy in patients who experience severe acute GI symptoms during RT [6,9,[11][12][13][14][15] . Preventing acute symptoms could be a strategy to help reduce the risk of delayed radiation effects, as, for example, attempted by use of prostaglandin analogues or probiotics [16,17] . Radiation enteropathy can be eradicated by surgery in some cases, but palliative surgical or medical interventions are the option of choice for the majority of patients.…”
Section: Discussionmentioning
confidence: 99%